Another approach for Leslie model via linear difference equations. Issue 5 (4th July 2021) - Ben Taher, R.; Naassi, N.; Elkettani, Y.; Rachidi, M.
Abstract: We explore here an approach to study the Leslie model, describing the growth of the discrete age structured populations. Our main tool is based upon properties of some linear difference equations. Involving the analytical and combinatorial aspects of solutions of these equations, we establish new formulas for the entries of the population vector and derive their asymptotic behavior. Significant illustrative examples and applications are given.